2018
DOI: 10.18520/cs/v115/i11/2079-2084
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Analysis of Uranium in Fazilka District, Punjab, India

Abstract: Laser fluorimetry technique has been used to estimate uranium concentration in groundwater samples collected from 20 villages of Fazilka district, Punjab, India. The uranium concentration was found to vary from 4.32 to 83.99 μg l -1 at different locations with mean concentration of 26.51 μg l -1 . Also, 24% of the drinking water samples exceeded the safe limits set by WHO, while 9% was above the limit set by AERB. Certain health risk factors like annual effective dose, excess cancer risk and lifetime average d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The higher value of uranium in the sample collected from a particular specific site of Dharchula could be due to the presence of igneous rocks in that region because studies have shown that the concentration of radionuclides like uranium in water depends upon its concentration in rocks and soil. Igneous rocks are usually those types of rocks that have a higher concentration of radionuclides like uranium in comparison to other kinds of rocks [7,21]. Thus, by analysis of different samples collected from different sites in the Tehsils and sub tehsils of Pithoragarh, it was found that the uranium concentration was found to be lower than the guideline values prescribed by both WHO and AERB (India).…”
Section: Uranium Concentration Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…The higher value of uranium in the sample collected from a particular specific site of Dharchula could be due to the presence of igneous rocks in that region because studies have shown that the concentration of radionuclides like uranium in water depends upon its concentration in rocks and soil. Igneous rocks are usually those types of rocks that have a higher concentration of radionuclides like uranium in comparison to other kinds of rocks [7,21]. Thus, by analysis of different samples collected from different sites in the Tehsils and sub tehsils of Pithoragarh, it was found that the uranium concentration was found to be lower than the guideline values prescribed by both WHO and AERB (India).…”
Section: Uranium Concentration Analysismentioning
confidence: 96%
“…Along with this, uranium emits alpha particles of high ionizing power, so it may be toxic if inhaled or ingested in excess amount. Eighty five percent of ingested uranium is contributed through drinking water and only 15% is contributed through food [7]. Uranium is a well-known nephrotoxic element and the principal sites of its deposition in the body are the kidney, liver, and bones.…”
Section: Introductionmentioning
confidence: 99%